Islam and the importance of peaceful - co-existence with other religions (with particular reference to Christianity) - Ashimi, Tijani Ahmad (2019)
Islam is a religion of peace, it is a religion to lead mankind from the depths of darkness and ignorance towards the path of light and knowledge. The literal meaning of Islam, derived from the Arabic word Salaam, means peace. The word “Islam” has another root derivation – Slim – which means surrender or submission. In short, Islam means peace acquired by humans by submitting their will to the Will of Allah. In the most serious note, one of God’s name and attribute is al-salam(The Most Peaceful), which means, peaceful co-existence and harmonious living are very important values that Islam urge Muslims to enjoy particularly with people of other faiths and religions, such as Christianity and others.. Based on this fact, the holy Qur’an is very serious in condemning any sort of ethnic or religious hostility towards other faiths, it instead promotes peaceful co-existence and religious tolerance; for the sake of humanity, love and human dignity. Thus, this humble paper by applying Quranic approach, aims to demonstrate the importance of peaceful co-existence in Islamic worldview, and how such peaceful living could be actualized in any pluralistic and multi-religious society. Finally, the paper will provide brief conclusion followed by some suggestions and recommendations.